NILAI RELIGIUS DALAM NOVEL SAGA DARI SAMUDRA KARYA RATIH KUMALA - Erlin Cahyani; La Ode Sahidin; Wa Ode Fitriani Sari; Asma Wati Ndita (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research examines the religious values in the novel Saga dari Samudra by Ratih Kumala. A novel is a long prose essay, containing a series of stories about a person's life and the people around him, highlighting the character and nature of each actor. Literary works created by authors must contain certain life values that will be conveyed to readers, various life values that the author wants to convey through his work, one of which is religious values. The formulation of the problem in this research is the religious values contained in the novel Saga dari Samudra by Ratih Kumala. The aim of this research is to describe the religious values in the novel Saga dari Samudra by Ratih Kumala. This research is a qualitative descriptive research. The data source in this research is the novel Saga dari Samudra published by Gramedia Pustaka Utama in 2023, which consists of 193 pages. Data collection techniques in this research were carried out using reading techniques and note-taking techniques. The data analysis technique in analyzing religious values in the novel Saga dari Samudra by Ratih Kumala uses a literary sociology approach. The results of the analysis show that religious values in the novel Saga dari Samudra by Ratih Kumala are religious values in human relationships with God, religious values in human relationships with themselves, and religious values in human relationships with other humans. Religious values in human relationships with God, which consist of worship, faith and gratitude. Religious values in humans' relationship with themselves, which consist of being patient, seeking knowledge, sincerity and introspection. Religious values in human relationships with other humans, which consist of forgiveness, mutual help, compassion, keeping promises, and upholding justice.